Application of the FreeStyle®Libre Glucose Monitoring System in type 1 diabetes mellitus patients aged 1–4 years. Issue 5 (14th June 2022) - Li, Yangshiyu; Cao, Bingyan; Chen, Qiong; Du, Mengmeng; Yan, Mingming; Chen, Yongxing; Wei, Haiyan; Wu, Xue; Cui, Yan; Liu, Fang
Abstract: Background: To investigate the analytical accuracy, safety performance, and user satisfaction (guardians of study participants) of the FreeStyle®Libre Glucose Monitoring System in the treatment of type 1 diabetes mellitus (T1DM), in children aged <4 years. Methods: Sixteen hospitalized children with new onset T1DM, aged 4 months to 4 years, were enrolled in this study. Patients wore the sensor for 14 days; sensor scans were performed immediately and at 5, 10, and 15 min after capillary blood glucose (BG) measurements to evaluate the effectiveness of the device and the lag effect. Results: The consensus error grid showed that 96.40% of values fell within zone A (no clinical impact) and 3.60% within zone B (little/no clinical impact). Overall, the mean absolute relative difference (MARD) was 9.34%, and was higher in the capillary BG <4.0 mmol/L group (15.18%) than in the 4–10 mmol/L (9.63%) and >10 mmol/L (7.17%) groups. The MARD increased gradually with scanning time extension, indicating a short lag effect. Regression analysis showed that a higher BG level was associated with a greater difference in FreeStyle®Libre System measurements. Conclusions: The use of the FreeStyle®Libre System in children aged 1–4 years is accurate and safe, and may be accurate down to 4 months, independent of patient characteristics.